A critical discourse analysis approach to news discourses and social practices on race in Brazil - Magalhães, Célia Maria (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2016)
In this paper I set out from Brazilian social theories on race to analyse a contemporary corpus of news reports in a Brazilian broadsheet newspaper. The aim is investigating change in mediated discourses on race. Based on Critical Discourse Analysis (CDA) and with the help of corpus linguistics methodological tools I focus on lexical items used to categorise race, the semantic relations created and their association with discourse representation in the newspaper. The combined analysis of semantic relations and interdiscursivity has allowed for the perception of tensions over the use of terms from different semantic fields to categorize race and of conflicting discourses of race classification in the paper. The analysis has also allowed for a cautious interpretation of dialogicality and of different orientations to racial difference, following the social research inventories in Fairclough (2003) in the reports.